Pendampingan Nilai-Nilai Agama Dan Moral Anak Usia Dini Di TK Dharma Wanita Besowo 3 Kepung Kediri - Denik Maghsyaniyah; Viren Afinta (LP3M IAIFA Kediri, 2022)
Understanding Early childhood in general are children aged under 6 years. Children aged 4 – 6 years or Kindergarten age (on the formal education path in accordance with the Law of the Republic of Indonesia Number 20 2003 article 28 concerning Early Childhood Education), is a period of sensitive for children, because this period is a time of maturation physical and psychological functions that are ready to respond to environmental stimulation and internalize it into the person. This period is the beginning physical, cognitive, language, social, emotional development, self-concept, discipline, independence, art, morals, and religious values. Therefore it is needed a condition and stimulation appropriate to the child's needs so that growth and development is achieved optimally. One of the basic attitudes that children must have to become human what is good and right is to have good attitudes and moral values ​​in act as God's people, children, family members and members Public. Age in Early Childhood Education is the most important time good and appropriate to lay the foundations of education values, morals, and religion to children. Although the role of parents is very large in building a moral and religious foundation for their children, the role of educators Early Childhood Education is also not small in laying the moral foundation and religion for a child.